Efektivitas mHealth untuk Meningkatkan Kontrol Glikemik dan Kepatuhan Diabetes Melitus Tipe 2 pada Pasien Dewasa - Hani Andriyana; Meira Erawati; Untung Sujianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effectiveness of Mobile Health (mHealth) in improving glycemic control and adherence in patients with type 2 diabetes mellitus. The method used is a systematic review. The results of this study are mHealth-based health interventions including blood sugar monitoring services with applications, short messages (SMS), voice calls via cell phones, video conferencing, and central call services conducted by health workers in 2-13 month intervals have benefits in increasing glycemic control and adherence in patients with type 2 diabetes mellitus. Services provided by health workers include health education, self-monitoring of blood sugar, diet counseling, healthy lifestyle tips, exercise, face-to-face counseling with health workers, stress management, and foot care. The conclusion of this study is that the mHealth program is effective in improving glycemic control and adherence in type 2 diabetes mellitus patients in addition to diabetes care in general